2017
DOI: 10.1017/ice.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Safe Injection Practices in Ambulatory Care

Abstract: Most recent infection outbreaks caused by unsafe injection practices in the United States have occurred in ambulatory settings. We utilized direct observation and a survey to assess injection practices at 31 clinics. Improper vial use was observed at 13 clinics (41.9%). Pharmacy support and healthcare worker education may improve injection practices. Infect Control Hosp Epidemiol 2017;38:614-616.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Understanding the SEIPS barriers and facilitators that prevent or assist safe injection practices can help guide clinical interventions to reduce disease risk exposure. In a recent study by Anderson et al, 15 HCWs self-reported a high knowledge of injection safety and no barriers to safe usage of medication vials; however, observation data collected in the same study revealed significant nonadherence to safe usage of medication vials. In addition, 2 other studies that collected anonymous survey data from clinicians reported that reuse of syringes for multiple patients still occurs in practice 16 …”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Understanding the SEIPS barriers and facilitators that prevent or assist safe injection practices can help guide clinical interventions to reduce disease risk exposure. In a recent study by Anderson et al, 15 HCWs self-reported a high knowledge of injection safety and no barriers to safe usage of medication vials; however, observation data collected in the same study revealed significant nonadherence to safe usage of medication vials. In addition, 2 other studies that collected anonymous survey data from clinicians reported that reuse of syringes for multiple patients still occurs in practice 16 …”
mentioning
confidence: 82%
“…13 The continued occurrence of unsafe medicationvial usage suggests that the knowledge of safe practices alone is not enough to ensure adherence. 14,15 The Systems Engineering Initiative for Patient Safety (SEIPS) model, which emphasizes persons, organization, technologies and tools, tasks, and environment 12 is one framework used to evaluate healthcare systems.…”
mentioning
confidence: 99%
“…33 In an observational study of 31 clinics, almost 20% stored single use vials for use on another patient. 34 Unsafe injection practices resulted in notification of more than 66,768 patients related to 38 events in 24 states between 2012 and 2018. 35 More than half of the events involved exposures occurring in a nonhospital setting (n = 21, 55%) and were identified on the basis of unsafe practices without documentation of disease transmission (n = 25, 66%).…”
Section: Discussionmentioning
confidence: 99%
“…Kossover-Smith et al [ 25 ] reported that there have been more than 50 outbreaks of viral and bacterial pathogens due to unsafe injection practices since 2001, a majority of which occurred in ambulatory settings [ 26 ]. Identified issues with injection safety include no access to hand hygiene [ 19 ], reuse of single-dose vials [ 27 ], reuse of a syringe, multidose vials not dated [ 28 ], drug diversion [ 26 ], and multidose vials entering a patient treatment area [ 28 ]. In 1 study regarding an outbreak of septic arthritis related to intra-articular injections, complex compounding was a culprit.…”
Section: Injection Safetymentioning
confidence: 99%